Animal welfare concerns at a fish farming operation in southeastern Brazil - Rodrigues,Diego Andre (2015)
Concerns for the welfare of fish during the farming/production process is in its infancy when compared to other species. This is due to disputes in the interpretation of characteristics that suggest awareness in fish, a concern that is somewhat widespread among consumers and producers. Through questionnaires, this study aimed to highlight what the members of a fishermens association (that farm Tilapia and Robalo Peva) understand about the welfare of fish, and whether it is considered during the production process. In addition, although there are still many controversies, this perception has been changing in recent years, in part due to anatomical, physiological and behavioral evidence that suggest fish are sentient (are aware of sensations, have subjective feelings). Moreover, as the consumer has become aware of the issues, concern for animal welfare has increased, leading to a need for the market to adapt to these requirements.